Clinicians' attitudes toward video games vary as a function of age, gender and negative beliefs about youth: A sociology of media research approach. (November 2015) - Ferguson, Christopher J.
Highlights: Clinicians were surveyed regarding their attitudes toward video games. No consensus among clinicians regarding video game effects was observed. Older clinicians and female clinicians were more likely to view games as harmful. Clinicians with negative attitudes toward youth were more likely to view games as harmful. Abstract: Debates regarding purported negative effects of video games have raged among scholars, clinicians and in the public arena. Surveys of both scholars and the general public reveal wide discrepancies in beliefs about the potential harmfulness of video games, and some evidence suggests that a "generational divide" may be at play. The current study examines this in a sample of 109 clinicians and clinical researchers. Beliefs about the potential harmfulness of video games varied widely in the sample, reflecting absence of a consensus. Beliefs about the harmfulness of video games were predicted by respondents' age, female gender and negative beliefs about youth. Contrary to hypotheses, respondents' neuroticism, openness, pacifism and previous gaming experience did not predict beliefs about video games. These results suggest that, even among clinicians, debates about video games are influenced by historical patterns of generational conflict with harmful beliefs endorsed mainly by older individuals who are hostile toward younger generations.